Approach to juvenile myasthenic crisis: case report (Research, Society and Development, 2021)
Introduction: Myasthenia gravis (MG) is an autoimmune disease that affects the neuromuscular junction, the production of antibodies together with the complement system, acts against nicotinic acetylcholine receptors (AChR), located in the postsynaptic membrane, resulting in significant impairment of the neuromuscular transmission. The classic clinical picture presents with fluctuating weakness and fatigability of the ocular, facial, bulbar or limb muscles. Myasthenic crisis, defined as respiratory failure associated with severe muscle weakness, is a potentially fatal complication that occurs in approximately 15%-20% of patients with MG. Objective: to demonstrate the approach to the myasthenic crisis, and the difficulty in diagnosing the myasthenic crisis, improving the prognosis of affected young people, identifying factors that may trigger the onset of symptoms, thus being able to qualify and anticipate the diagnosis of the crisis and treatment, in order to that inadequate procedures do not occur to patients with the disease. Methodology: this is a clinical case study with a qualitative and descriptive perspective, which consists of a research that, in general, takes place with direct data collection, in which the researcher is the indispensable instrument. Case report: This is an 11-year-old female patient, black, with a previous diagnosis of Myasthenia Gravis 6 months ago, with diffuse proximal muscle weakness, admitted for zero vacancy in the emergency care unit of the hospital in question with acute respiratory muscle failure, superficial sedation, administration of fentanyl and midazolam, and she was referred to the intensive care unit, maintaining mechanical ventilation. Conclusion: in view of the case reported, the importance of an accurate diagnosis, quick and effective care is noted, always keeping in mind the stabilization of the crisis, ventilatory support, and specialized pharmacological treatment, using immunoglobulin that showed good efficacy. in the treatment, and having a multidisciplinary team in an intensive care unit, consisting of a respiratory physiotherapist, mainly in respiratory conditions, to offer adequate support for the treatment of rare diseases and better ventilation management in the case of juvenile patients with myasthenia gravis.